Design and characterization of novel dirhodium coordination polymers – the impact of ligand size on selectivity in asymmetric cyclopropanation. Issue 10 (7th April 2021) - Li, Zhenzhong; Rösler, Lorenz; Wissel, Till; Breitzke, Hergen; Hofmann, Kathrin; Limbach, Hans-Heinrich; Gutmann, Torsten; Buntkowsky, Gerd
Abstract : Novel dirhodium coordination polymers are synthesized and characterized by various spectroscopic techniques. The catalysts exhibit good stability and excellent catalytic performance and selectivity in the cyclopropanation of diazooxindoles. Abstract : Three chiral dirhodium coordination polymers Rh2 –L n ( n = 1–3) have been synthesized via ligand exchange between dirhodium trifluoroacetate Rh2 (TFA)4 and differently sized chiral dicarboxylic acids derived from l - tert -leucine. SEM images indicate that the Rh2 –L n ( n = 1–3) polymers have a lamellar structure. XPS data demonstrate that the oxidation state of rhodium in the dirhodium nodes is maintained during the synthesis of the polymers. The coordination polymers have been further characterized by FTIR, 1 H → 13 C CP MAS NMR and 19 F MAS NMR spectroscopy to prove the formation of polymers via ligand exchange. Although the quantitative 19 F MAS NMR spectra reveal incomplete ligand substitution in the coordination polymers, these catalysts show excellent activity and selectivity in the asymmetric cyclopropanation reaction between styrene and diazooxindole. In particular, the enantioselectivity has been significantly improved compared with previously designed dirhodium coordination polymers, which were synthesized from aromatic dicarboxylic acids derived from l - phenylalanine. Meanwhile, the dirhodium polymers can be easily recycled five times without significant reduction in their catalytic efficiency.